Enhancing IoT Data Security: AES Encryption for Protecting Data in Transit- A Case Study in Smart Agriculture - Imam Asrowardi; Septafiansyah Dwi Putra; Eko Subyantoro; Bita Parga Zen (JURNAL INFOTEL, 2025)
The integration of IoT in smart agriculture facilitates real-time environmental monitoring and efficient farming operations. However, the sensitive nature of data in transit presents significant security challenges, primarily due to threats like data interception and unauthorized access. This study explores the implementation of AES-128 encryption as a solution to secure data transmission within a smart agriculture IoT system. Utilizing NodeMCU microcontrollers with DHT22 sensors, this research investigates the encryption and decryption of environmental data (temperature and humidity) through the MQTT protocol, with Node-RED providing data visualization. Experimental results indicate that AES-128 encryption adds minimal overhead, maintaining real-time system performance while safeguarding data integrity and confidentiality. This encryption framework not only reinforces secure data transmission but also enhances decision-making reliability in agricultural management, underscoring the practical benefits of data security in IoT-based smart farming.